Portable remote socket / Afif Nor Norazman, Firdaus Hashim and Khuzaifi Akili Darami - Norazman, Afif Nor; Hashim, Firdaus; Darami, Khuzaifi Akili (2015)
The Portable Remote Socket (PRS) is a portable socket that has capabilities to turn ON and OFF the socket by using remote. The remote can be used within eight meters without obstacles and six meters with obstacles. This project was invented with a main purpose to help the elderly and handicap peoples that have physical problem that contribute to limited movement. In addition, as an alternative, this device also allows the users to control the socket by using pushbuttons on the device. This project consist two parts of working flow which is receiving signal and relay control. For receiving command part, the controller (Arduino) will receive signal either from pushbuttons or remote. When the remote or pushbutton is pressed, it will trigger to “HIGH” with pulse width modulation (PWM) signal. On the others part, after processing the input, controller (Arduino) will send command in order to trigger the relays through transistors which act as electronic switch. Each of the sockets is connected with indicator light that will operate simultaneously with the socket.